2012
DOI: 10.1055/s-0031-1299596
|View full text |Cite
|
Sign up to set email alerts
|

Role of Estrogen Receptor-β in Endometriosis

Abstract: Endometriosis is an estrogen-dependent disease. The biologically active estrogen, estradiol, aggravates the pathological processes (e.g., inflammation and growth) and the symptoms (e.g., pain) associated with endometriosis. Abundant quantities of estradiol are available for endometriotic tissue via several mechanisms including local aromatase expression. The question remains, then, what mediates estradiol action. Because estrogen receptor (ER)β levels in endometriosis are >100 times higher than those in endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(203 citation statements)
references
References 65 publications
(69 reference statements)
4
184
0
2
Order By: Relevance
“…Estrogen and progesterone exert their biological functions through binding to their specific receptors in the endometrium, and the expression levels of these receptors are periodically changed in accordance with the normal menstrual cycle of healthy women (Bulun et al, 2012;Henriet et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen and progesterone exert their biological functions through binding to their specific receptors in the endometrium, and the expression levels of these receptors are periodically changed in accordance with the normal menstrual cycle of healthy women (Bulun et al, 2012;Henriet et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated E2 metabolism has been reported to contribute to a variety of human diseases including leiomyoma, endometriosis, osteoporosis, Parkinson disease, and gynecological malignancies (31)(32)(33)(34)(35). Recently, Flamini et al (36) reported that E2 could regulate endometrial cell cytoskeletal remodeling and motility via focal adhesion kinase.…”
Section: Anxa2 Knockdown Compromises Growth Metastasis and Proangiomentioning
confidence: 99%
“…PGE2, as well as the EGF, upregulate aromatase (CYP19) expression, the enzyme that plays a key role in estrogen (E2) biosynthesis (20)(21). The biologically active E2 aggravates pathologic processes including inflammation and influences the risk of cancer through an inflammation-related mechanism (22)(23)(24). Lately, the aromatase (CYP19A1) has been identified in malignant mesothelioma (25).…”
Section: Malignant Mesothelioma Molecular Targets Involved In Inflammmentioning
confidence: 99%